Smart Seirs (special education information retrieval system) - Hassim, Hasniza; Mohd Helmi, Mohd Firdaus; Mohamad Tanuri, Zati Atiqah; Mohamed Sawal, Mohd Zool Hilmie; Arif, Zuraidah (Universiti Teknologi MARA, Kedah, 2018)
SMART SEIRS (Special Education Information Retrieval System) is an assessment of the practicability of the Quick Response code and portable devices in the context of overcoming learning disabilities for the students with special needs. The attentiveness was exclusively to discover the way portable devices and QR codes applications may enrich and blend teaching and learning activities. This is also to explore whether the QR code applications are motivating enough to the students with differently-abled in coping with learning disabilities, hence brought much deviation to the traditional method of teaching and learning. The data were collected from the teachers‟ interview and pupils‟ survey and observation. Novelty and uniqueness: SMART SEIRS (Special Education Information Retrieval System) provides an alternative technique and scheme for the special education vocational teachers and library media teachers in order to assist their differently-abled students for the implementation of empowering the information search and retrieval skills in classroom setting. This is also exciting for the students with differently-abled to get engaged with much-wanted distinction to the traditional school day. Moreover, this is the first collaborative interactive blended learning project involving academician and special education vocational teachers that implements interactive group learning session via QR code applications, according to special group of students.